Ancient Origin of the CARD–Coiled Coil/Bcl10/MALT1-Like Paracaspase Signaling Complex Indicates Unknown Critical Functions - Staal, Jens; Driege, Yasmine; Haegman, Mira; Borghi, Alice; Hulpiau, Paco; Lievens, Laurens; Gul, Ismail Sahin; Sundararaman, Srividhya; Gonçalves, Amanda; Dhondt, Ineke; Pinzón, Jorge H.; Braeckman, Bart P.; et al. (Frontiers in Immunology, 2018)
The CARD-CC/Bcl10/MALT1-like paracaspase (CBM) signaling complexes composed of a CARD-coiled-coil (CC) family member (CARD9, -10, -11 or -14), Bcl10 and the type 1 paracaspase MALT1 play a pivotal role in immunity, inflammation and cancer. Targeting MALT1 proteolytic activity is of potential therapeutic interest. However, little is known about the evolutionary origin and the original functions of the CBM complex. Type 1 paracaspases originated before the last common ancestor of planulozoa (bilaterians and cnidarians). Notably in bilaterians, Ecdysozoa (e.g. nematodes and insects) lack Bcl10 whereas other lineages have a Bcl10 homolog. A survey of invertebrate CARD-CC homologs revealed such homologs only in species with Bcl10, indicating an ancient common origin of the entire CBM complex. Furthermore, vertebrate-like Syk/Zap70 tyrosine kinase homologs with the ITAM-binding SH2 domain were only found in invertebrate organisms with CARD-CC/Bcl10, indicating that this pathway might be related to the original function of the CBM complex. Moreover, the type 1 paracaspase sequences from invertebrate organisms that have CARD-CC/Bcl10 are more similar to vertebrate paracaspases. Functional analysis of protein-protein interactions, NF-κB signaling and CYLD cleavage for selected invertebrate type 1 paracaspase and Bcl10 homologs support this scenario and indicate an ancient origin of the CARD-CC/Bcl10/paracaspase signaling complex. In contrast, many of the known MALT1-associated activities evolved fairly recently, indicating that unknown functions are at the basis of the protein conservation. As a proof-of-concept, we provide initial evidence for a CBM- and NF-κB-independent neuronal function of the C. elegans type 1 paracaspase malt-1. In conclusion, this study shows how evolutionary insights may point at alternative functions of MALT1.